New-onset Graves’ disease following SARS-CoV-2 vaccination: a case report - Ringo Manta; Charlotte Martin; Vinciane Muls; Kris G Poppe (European Thyroid Journal, 2023)
A 22-year-old male with a history of ulcerative colitis and nephrotic syndrome treated with immunomodulatory agents including vedolizumab and mycophenolic acid developed hyperthyroidism 2 weeks following the first administration of BNT162b2 vaccine (Pfizer- BioNTech COVID-19 vaccine). Graves’ disease (GD) was diagnosed based on the elevated thyrotropin-receptor antibody, thyroid scintigraphy and ultrasound. To this day, four cases of new-onset GD following SARS-CoV-2 vaccine were reported in patients with no previous history of thyroid disease. Two cases of recurrence of GD following SARS-CoV-2 vaccine were also reported. Although the underlying mechanisms of vaccine-induced autoimmunity remain to be clarified, there is a rationale for the association between SARS-CoV-2 vaccination and the development of Th1-mediated diseases, at least in predisposed individuals. The BNT162b2 vaccine could be a trigger for GD in some patients. However, the benefit/risk ratio remains by far in favour of SARS-CoV-2 vaccination considering the potentially higher risk of severe infection in these patients.